2019
DOI: 10.1111/ctr.13574
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B core‐related antigen to detect hepatitis B virus (HBV) reactivation in heart transplant recipients with past HBV infection: A pilot study

Abstract: Hepatitis B virus (HBV) reactivation in immunosuppressed HBsAg−/anti-HBc+/HBV-DNA− patients has been described in various clinical settings. We recently analyzed this phenomenon in 11 heart transplant recipients with markers of prior HBV infection (anti-HBc+/±anti-HBs+/HBVDNA−, thereafter referred to as "past HBV"), searching HBV-DNA by high-sensitivity qualitative nested PCR in sera obtained before transplant and for a median period of 30 months after transplant. 1 A definite HBV reactivation (HBV-DNA detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The levels of hepatitis B core‐related antigen and anti‐HBs are known to be useful for predicting HBV reactivation, and are surrogate markers for cessation of NA in patients being treated for HBV reactivation 19–21 . Previously, it was reported that HBV DNA did not rise to the level of quantification after cessation of NA in the patients with anti‐HBs ≥10 mIU/ml at the time of NA cassation 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The levels of hepatitis B core‐related antigen and anti‐HBs are known to be useful for predicting HBV reactivation, and are surrogate markers for cessation of NA in patients being treated for HBV reactivation 19–21 . Previously, it was reported that HBV DNA did not rise to the level of quantification after cessation of NA in the patients with anti‐HBs ≥10 mIU/ml at the time of NA cassation 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, histological diagnosis is difficult to establish in a viral infection that is associated with inflammation and necrosis, especially when there are no microorganisms directly associated with the infection. Sometimes it is difficult to differentiate a virus-induced lesion from an acute rejection (26,27). In these instances the results of the initial biopsy (with differential diagnosis difficulties) are compared with the results of subsequent biopsies, performed after specific treatment for the infection have already been administered.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no single generally accepted term for a condition that occurs after the resolution of acute or chronic hepatitis B and is characterized by a special set of serological viral markers: negative HBsAg and positive anti-HBc class IgG (in combination with anti-HBs or not). To describe subjects with such a serological profile, when no certain data on the disease history are available, different definitions are used in the literature: “previous HBV infection”[ 22 ], “past exposure to hepatitis B”[ 23 ], “past HBV infection”[ 24 ], “resolved HBV infection”[ 25 ], and even “anti-HBc alone”[ 26 ]. In case of a sustained HBsAg loss and undetectable level of HBV DNA, combined with the absence of clinical or histological signs of active viral infection in an individual who was previously HBsAg-positive, the term “resolved chronic hepatitis B” is proposed[ 27 ].…”
Section: Suggestions For the Common Terminology And Revision Of Optim...mentioning
confidence: 99%